The Chloroplast Basics and Applications - Rebeiz, Constantin A.; Benning, Christoph; Bohnert, Hans J.; Daniell, Henry; Hoober, J. Kenneth; Lichtenthaler, Hartmut K.; Portis, Archie R.; Tripathy, Baishnab C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The world population is expected to increase to 9 billion by the year 2050 which will generate food and fuel shortages. Since it will be difficult to increase the land area under cultivation without serious environmental consequences, higher productivity for biomass is required. Improvement in photosynthetic efficiency would require increased knowledge and deeper understanding of :(a) the biosynthesis of photosynthetic membrane components such as hemes, chlorophylls, carotenoids, quinones, and lipids; (b) photosynthetic membrane apoprotein biosynthesis; (c) the biosynthesis and regulation of the assembly of pigment-apoprotein complexes; and (d) the complexities of carbon sensing, biosynthesis and allocation. These goals may be accomplished by bioengineering of chloroplasts with higher photosynthetic efficiency and superior adaptation to various stresses and/or alteration of the kinetic properties of the CO2-assimilating enzyme, Rubisco. Advances towards this goal are addressed in this volume that will foster cooperation between biochemists and molecular biologists, scientists involved in photosynthesis research and biotechnologists involved in plant and plastid genomics and transformation. We envision future research to focus attention on "Chloroplast Bioengineering" as an integrated novel field of research. This book is designed for graduate students and researchers in chlorophyll metabolism, integrative plant biology, plant physiology, plant biochemistry, plant molecular biology, biotechnology, bioenergy and biofuels.
1. Investigation of Possible Relationships between the Chlorophyll Biosynthetic Pathway, the Assembly of Chlorophyll-Protein Complexes and Photosynthetic Efficiency -- 2. Evidence for Various 4-Vinyl Reductase Activities in Higher Plants -- 3. Control of the Metabolic Flow in Tetrapyrrole -- 4. Regulation and Functions of the Chlorophyll Cycle -- 5. Magnesium Chelatase -- 6. The Enigmatic Chlorophyll a Molecule in the Cytochrome bb6(Bf Complex -- 7. The Non-mevalonate DOXP/MEP Pathway (Deoxyxylulose 5-Phosphate/Methylerythritol 4-Phosphate Pathway) of Chloroplast Isoprenoid and Pigemtn Biosynthesis -- 8. The Methylerythritol 4-Phosphate Pathway: Regulatory Role in Plastid Isoprenoid Biosynthesis -- 9. The Role of Plastids in Protein Geranylgeranylation in Tobacco BY-2 Cells -- 10. The Role of the Methyl-Erythritol-Phosphate Pathway in Rhythmic Emission of Volatiles -- 11. Tocochromanols: Biological Function and Recent Advances to Engineer Plastidial Biochemistry for Enhanced Oil Seed Vitamin E Levels -- 12. The Anionic Chloroplast Membrane Lipids Phosphatidylglycerol and Sulfoquinovosyldiacylglycerol.-13. Biosynthesis and Function of Monogalactosyldiacylglycerol, the Signature Lipid of Chloroplasts -- 14. Synthesis and Functiion of the Galactolipid Digalactosyldiacylglycerol -- 15. The Chemistry and Biology of Light-Harvesting Complex II and Thylakoid Biogenesis -- 16. Folding and Pigment Binding of Light-Harvesting Chlorophyll a/b Protein -- 17. The Plastid Genome as a Platform for the Expression of Microbial Resistance Genes -- 18. Chloroplast Genetic Engineering: A Novel Technology for Agricultural Biotechnology and Bio-pharmaceutical Industry -- 19. Engineering the Sunflower Rubisco Subunits into Tobacco Chloroplasts: New Considerations -- 20. Engineering Photosynthetic Enzymes Involved in COb2 (B- Assimilation by Gene Shuffling -- 21. Elevated COb2 (Band Ozone: Their Effects on Photosynthesis -- 22. Regulation of Photosynthetic Electron Transport -- 23. Mechanisms of Drought and High Light Stress Tolerance Studied in a Xerophyte, Citrullus Ianatus (Wild Watermelon) -- 24. Antioxidants and Photo-oxidative Stress Responses in Plants and Algae -- 25. Singlet Oxygen-Induced Oxidative Stress in Plants.s
Keywords: Life sciences; Biochemistry; Proteomics; Cytology; Plant physiology; Life Sciences; Plant Physiology; Plant Biochemistry; Cell Biology; Proteomics